A Novel, Reliable and Highly Versatile Method to Evaluate Different Prion Decontamination Procedures - Eraña, Hasier; Pérez-Castro, Miguel Ángel; García-Martínez, Sandra; Charco, Jorge M.; López-Moreno, Rafael; Díaz-Dominguez, Carlos M.; Barrio, Tomás; González-Miranda, Ezequiel; Castilla, Joaquín (Frontiers in Bioengineering and Biotechnology, 2020)
Transmissible spongiform encephalopathies are a group of invariably fatal neurodegenerative disorders. The causal agent is an aberrantly folded isoform (PrPSc or prion) of the endogenous prion protein (PrPC) which is neurotoxic and amyloidogenic and induces misfolding of its physiological counterpart. The intrinsic physical characteristics of these infectious proteinaceous pathogens makes them highly resistant to the vast majority of physicochemical decontamination procedures used typically for standard disinfection. This means prions are highly persistent in contaminated tissues, the environment (surfaces) and, of great concern, on medical and surgical instruments. Traditionally, decontamination procedures for prions are tested on natural isolates coming from the brain of infected individuals with an associated high heterogeneity resulting in highly variable results. Using our novel ability to produce highly infectious recombinant prions in vitro we adapted the system to enable recovery of infectious prions from contaminated materials. This method is easy to perform and, importantly, results in highly reproducible propagation in vitro. It exploits the adherence of infectious prion protein to beads of different materials allowing accurate and repeatable assessment of the efficacy of disinfectants of differing physicochemical natures to eliminate infectious prions. This method is technically easy, requires only a small shaker and a standard biochemical technique and could be performed in any laboratory.